2019
DOI: 10.1186/s12891-019-2432-4
|View full text |Cite
|
Sign up to set email alerts
|

Distal femoral reconstruction following failed total knee arthroplasty is accompanied with risk for complication and reduced joint function

Abstract: BackgroundSubstantial bone loss following failed total knee arthroplasty (TKA) represents a major challenge in revision arthroplasty, that can require distal femoral reconstruction (DFR). In this study, we aimed to assess the clinical outcome and the complication frequencies of individuals who underwent DFR with modular megaprostheses. Additionally, we aimed to compare functional outcome measures after DFR in these sophisticated cases to an age-matched control group of total knee prostheses to quantify the pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
41
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(41 citation statements)
references
References 37 publications
0
41
0
Order By: Relevance
“…The Knee Society Score improved from a preoperative median of 20 to a postoperative median of 80 [27]. Out of three studies, only Vertesich et al [27] mentioned revision and implant survival in their study. Revision was required in three cases, and the implant survival was 74.8% at 1 year and 40.9% at 10 years ( Table 4).…”
Section: Distal Femur Megaprosthesis (N = 54)mentioning
confidence: 97%
“…The Knee Society Score improved from a preoperative median of 20 to a postoperative median of 80 [27]. Out of three studies, only Vertesich et al [27] mentioned revision and implant survival in their study. Revision was required in three cases, and the implant survival was 74.8% at 1 year and 40.9% at 10 years ( Table 4).…”
Section: Distal Femur Megaprosthesis (N = 54)mentioning
confidence: 97%
“…The leading cause of complication in the septic cohort was infection, whereas aseptic loosening, structural failure, and infection were predominant causes in the aseptic cohort. There have been several reports on clinical outcomes of megaprosthesis implantation in nononcologic patients [5,[12][13][14][15][16]. Parvizi et al studied 48 patients who underwent revision arthroplasty with proximal femoral replacement for nononcologic conditions [16].…”
Section: Discussionmentioning
confidence: 99%
“…High complication rates for distal femoral replacement have been demonstrated in several studies [5,12,13]. Despite this, authors highlight the benefits of improved patient-reported outcomes, earlier mobilization, and limb salvage as reasons to consider a megaprosthesis in appropriately selected patients.…”
Section: Discussionmentioning
confidence: 99%
“…Megaprosthetic replacement is commonly performed in lower-limb reconstruction after tumor resections [ 16 , 17 , 18 , 19 ] as well as increasingly after trauma [ 20 , 21 , 22 ] or failed primary endoprosthetic replacement [ 23 , 24 ]. Despite their high rates of long-term sequelae including infection, mechanical and soft tissue failures, and loosening, patients benefit from surgery by being able to use their lower extremities in activities of daily living.…”
Section: Discussionmentioning
confidence: 99%